From the Polis to the Group and back - Franco Di Maria (Forum for Group Psychotherapies and Processes)
This contribution explores the relational quality of humans, underlining the political nature of their psyche, with its intrinsic connections to culture, ethics and society. To deal with the political transpersonal, when it comes to the work with the unconscious, means to acknowledge we are part of a system where individuals are not seen as “subjects” but as “participants”, in a network of shared laws and ethics. Specifically, ethics concerns the quality of the intersubjective relationships, as it does not only concern knowing how to do or knowing how to be, but the making of being. In other words, ethics deals with the relational nature of the subject. The nature of such relational subjectivity is political and its most evident quality is ethical: politics is intertwined with culture, not as the obvious background where human evolution and civilization takes place, but as a co-protagonist in the constitution of the mental schemes that support the man-world relationship. The transit from the idea of an individual subject to a collective subjectivity belongs to the process of socialization of the mental experience. Both from an inter-subjective and groupanalytical perspective, human beings prematurely internalize relationships and form “internal groupalities”. The concept of a collective structure of the psyche implies that mental phenomena are metaphorical representations and cannot only be reductively explained in terms of combination-interaction between physiochemical elements. The proposal that stems from this contribution, therefore, is to transform our relationship with the ways of knowing, of doing scientific research, of practicing in our clinical practices, by challenging our mental organizations and the institutions that we inhabit.